Sosialiasi Pencegahan Hipertensi Pada Remaja di Sekolah Melalui Gerakan Jaga Jantung Dengan Gerak Aktif Senam Jantung Sehat - Yuningsih, Aneng; Suprapti, Betty; Kurnia, Anih; Gustiani, Mia Ruhmiati; Asparina, Arina; Ismawi, Ade Sayid; Purnama Sari, N.Jihan Audiya (Yayasan Inspirasi El Burhani, 2025)
Abstract Hypertension is a chronic condition with a high prevalence, increasing the risk of cardiovascular diseases such as stroke, heart attack, and kidney failure. Recent data suggest that hypertension affects not only adults but also adolescents, with a rising prevalence. Major risk factors include an unhealthy lifestyle, obesity, genetic predisposition, and lack of physical activity. Preventive efforts are essential to increase awareness among adolescents about maintaining heart health through physical activity. This community service program aimed to enhance adolescents' understanding of hypertension risks and prevention through the